DAMPAK COVID-19 TERHADAP PEREKONOMIAN MASYARAKAT DAN PEMBANGUNAN DESA RABASAN KEC. CAMPLONG KAB. SAMPANG - Lutfiyanto (STIE Bakti Bangsa Pamekasan, 2022)
The article aims to examine the impact of Covid-19 on the community's economy and village development. The village always gets help, leads to circumstances or gives birth to the village losing its identity. The loss of the village's identity is proven by the existence of whatever is required by the government in its transmission, it must get rewards in the form of material. The basic problem is how to fulfill the economy as a basic human need in order to carry out activities in the world in order to fulfill welfare, safety. The relationship between village democracy with the direction of the economy and village development which is an inseparable unit. Democracy influences the handling of Covid-19, is a real test of the results of village democracy in realizing the economy and development. The research is intended to understand the impact of outbreaks on the village economy, rural development that is sweeping the world. The views of the village community have experienced a crisis of confidence, due to the role played by the central and regional governments that do not pay attention to the village as an independent government losing its identity. For the sake of the realization of a village democracy in the field of economy and development, ideally building the character of a society free from dependency.